Efficient synthesis of a hydroxyethylamine (HEA) isostere and its alpha-aminophosphonate and phosphoramidate derivatives as potential anti-HIV agents - Bhattacharya, Asish K.; Rana, Kalpeshkumar C.; Pannecouque, Christophe; De Clercq, Eric (Chemmedchem, 2012)
HIV protease is a promising drug target for AIDS therapy, and several potent HIV-1 protease inhibitors have been reported to date. Although existing inhibitors exhibit high selectivity, they have also been associated with severe side effects and the possible emergence of therapeutic resistance. As HIV protease cleaves the peptide bond via a tetrahedral intermediate, various transition-state models such as hydroxyethylamine (HEA) have been designed. We therefore pursued an efficient synthesis of an HEA isostere; this was performed with a novel one-pot reductiontransiminationreduction reaction sequence as a key step. a-Aminophosphonate and phosphoramidate derivatives of the HEA isostere were designed and synthesized, and all of the synthesized derivatives were assayed for their anti-HIV activities against wild-type and mutant HIV strains. Phosphoramidate derivative 15?a was found to be the most active of all synthesized compounds against the IIIB and RES056 strains. As phosphonates are known to exhibit physiological stability, good cell permeability, and other promising pharmacokinetic characteristics, our newly synthesized compounds have the potential as alternatives to existing therapeutics and diagnostics.
Keywords: a-aminophosphonates; antiviral agents; hydroxyethylamine isosteres; phosphoramidates; synthesis